External Ophthalmomyiasis Caused by a Rare Infesting Larva, Sarcophaga argyrostoma - Shmuel Graffi; Avi Peretz; Amos Wilamowski; Heather Schnur; Fouad Akad; Modi Naftali (Case Reports in Ophthalmological Medicine)
Purpose. External ophthalmomyiasis (EO) is caused by infesting larvae belonging to various species of flies. Most documented cases result from sheep (Oestrus ovis) and Russian (Rhinoestrus purpureus) botfly larvae, but we recently discovered a rare case of EO caused by flesh fly (Sarcophaga argyrostoma) larvae. Here, we report the case of a patient with EO who had been hospitalized and sedated for 1 week because of unrelated pneumonia. Methods. Case report. Results. A total of 32 larvae were removed from the adnexae of both eyes. Larvae identification was confirmed through DNA analysis. Treatment with topical tobramycin resulted in complete resolution of EO. Conclusion. EO can be caused by S. argyrostoma, and the elderly and debilitated may require extra ocular protection against flies during sedation.